Combination Learning Models With Technology To Hone Critical Minding Patterns On National Insights - Purba, Ramen Antonov (Jurnal Pendidikan dan Pengajaran, 2022)
The research was conducted to hone students' critical thinking in citizenship courses on national insight by combining a time token type cooperative model with a zoom application. Method With quasi-experimental design. The control and experimental samples were a total of 62 students. The control group learns citizenship with WhatsApp, and the experimental group learns with a cooperative combination of time token type with the zoom application. Data analysis with Homogeneity Test, Normality Test, and Hypothesis Testing. The result of Sig value two-tail is 0.00, which is smaller than 0.05. Ho is unacceptable, and Ha is acceptable. Combining the time token type of cooperative learning model with the zoom application can hone students' critical thinking patterns. Better than students learning to use Whatsapp